Concise Manual for Ceramic Studies From the Nile Valley to the Middle East - David, Romain (Africae Studies, 2022)
This manual is intended to accompany the training of future ceramic specialists in the Arab world. Resulting from the collaboration of four major institutions of French archaeology abroad: the Section française de la direction des Antiquités du Soudan (Sfdas), the Institut français d'Archéologie orientale (Ifao), the Institut français du Proche-Orient (Ifpo) and the Centre français de recherche de la péninsule arabique (Cefrepa), it draws on the recent work of specialists from the Nile Valley, the Near East and the Arabian Peninsula to shed light on the theoretical reflections that have enriched ceramic studies in recent decades. Providing a genuine field tool, this volume is nonetheless a skilfully illustrated collection of the contribution of ceramic studies to the understanding of human history. This is the English version of the manual. The bilingual version (English / Arabic) is available here: https://page.hn/yq8gch.